2022
DOI: 10.3390/su14020638
|View full text |Cite
|
Sign up to set email alerts
|

Response of Rice (Oryza sativa L.) Cultivars to Variable Rate of Nitrogen under Wet Direct Seeding in Temperate Ecology

Abstract: Transplanting rice appears to pose many problems, including depletion of freshwater reservoirs and competition for labor. Conversely, direct seeding allows us to overcome shortcomings associated with conventional transplanting. Nitrogen is a crucial nutrient needed for plant growth and yield. Therefore, this study was executed to analyze the influence of nitrogen on the performance of rice genotypes grown by direct seeding in wet soil. The experiment comprised various rice cultivars, i.e., Shalimar Rice-1, Sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…might have enhanced the productivity of the variety which enhanced the gross returns, net returns and benefit cost ratio. These results are in line with Rai et al [21] and Jehangir et al [24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…might have enhanced the productivity of the variety which enhanced the gross returns, net returns and benefit cost ratio. These results are in line with Rai et al [21] and Jehangir et al [24].…”
Section: Discussionsupporting
confidence: 91%
“…These results are in line with Dar et al [23]. Jehangir et al [24] also reported that many workers found that there was a significant increase in grain, straw and biological yield of rice variety with a limited dose of nitrogen ha -1 .…”
Section: Yield Attributes and Yieldsupporting
confidence: 89%
“…These findings show that the study of drip irrigation rice is of great value for promoting largescale upland rice production and improving water and nitrogen utilization efficiency in arid areas. However, the yield and NUE of the two cultivars were not significantly different from those under alternate dry−wet irrigation, which may be related to the cultivars (Jehangir et al, 2022), ecological conditions (Naeem et al, 2022), soil types (Ye et al, 2019), and cultivation methods (Sandhu and Mahal, 2014).…”
Section: Appropriate Water and Nitrogen Management Increases The Yiel...mentioning
confidence: 90%